Patients with locally advanced and metastatic cutaneous squamous cell carcinoma treated with immunotherapy in the era of COVID-19: stop or go? Data from five Italian referral cancer centers. (November 2020) - Saponara, Maristella; Pala, Laura; Conforti, Fabio; Rubatto, Marco; De Risi, Ivana; Spagnolo, Francesco; Guida, Michele; Bossi, Paolo; Quaglino, Pietro; Queirolo, Paola
Since the end of 2019, global healthcare systems have been dealing with the COVID-19 pandemic. In oncology, the biggest questions concern interaction of COVID-19 with pre-existing cancer disease and with systemic anticancer treatments. With regards to immunotherapy, there is uncertainty about its effect in the context of COVID-19 in terms of probability and course of viral infection. Herein, we retrospectively report data of patients with advanced cutaneous squamous cell carcinoma (cSCC) treated with immunotherapy at five Italian referral cancer centers during the pandemic. cSCC is a disease poorly represented in the literature, typically affecting fragile, elderly patients, with multiple comorbidities and often immunosuppressed. Overall, 54 patients were identified, most of them coming from Lombardy and Piedmont, the two regions hit hardest by COVID in Italy. In most cases, our choice was to continue treatment, reserving temporary interruptions only to patients considered particularly at risk for age and comorbidity. A total of 9% of patients developed new-onset symptoms or had chest radiological assessment potentially related to COVID-19. Nasopharyngeal swabs were collected in all suspicious cases and two hospitalized patients were found to be positive. In conclusion, the outbreak of COVID-19 is a major worldwide health concern. Our data indicate that COVID-19 mortality in patients with cancer may be principally driven by advancing age, the presence of other comorbidities, and other cancer-related conditions (i.e. hospitalization). Our data further suggests the safety of continued use of PD-1 blockade during the COVID-19 pandemic (obviously implementing all the safety measures in the hospital environment) also considering the possible negative effects of a prolonged suspension on the course of the tumor evolution. We think it is useful to collect and report case studies coming from reference centers, because they can represent helpful examples for the scientific community of clinical management of patients affected by cancer in this difficult period and guide further research.